Evaluación de las prácticas sostenibles en algunas empresas constructoras en Bogotá para el año 2024 (2024)
This thesis evaluates sustainability activities in the construction sector in Bogotá, approaching the subject from a business administration perspective. Amidst the growing importance of sustainability in business management, this work delves into the changing dynamics of the construction sector in the Colombian capital.